CROSS Versus FLOT Regimens in Esophageal and Esophagogastric Junction Adenocarcinoma: A Propensity-Matched Comparison. Issue 5 (25th November 2022) - Donlon, Noel E.; Moran, Brendan; Kamilli, Anitha; Davern, Maria; Sheppard, Andrew; King, Sinead; Donohoe, Claire L.; Lowery, Maeve; Cunningham, Moya; Ravi, Narayanasamy; Mueller, Carmen; Cools-Lartigue, Jonathan; et al.
Abstract : Background: The FLOT protocol and the CROSS trimodality regimen represent current standards in the management of locally advanced esophageal adenocarcinoma. In the absence of published Randomised Controlled Trial data, this propensity-matched comparison evaluated tolerance, toxicity, impact on sarcopenia and pulmonary physiology, operative complications, and oncologic metrics. Methods: Two hundred and twenty-two patients, 111 in each arm, were included from 2 high-volume centers. Computed tomography-measured sarcopenia, and pulmonary function (forced expiratory volume in first second/forced vital capacity/diffusion capacity for carbon monoxide) were compared pretherapy and posttherapy. Operative complications were defined as per the Esophageal Complications Consensus Group (ECCG) criteria, and severity per Clavien-Dindo. Tumor regression grade and R status were measured, and survival estimated per Kaplan-Meier. Results: A total of 83% were male, cT3/cN+ was 92%/68% for FLOT, and 86%/60% for CROSS. The full prescribed regimen was tolerated in 40% of FLOT patients versus 92% for CROSS. Sarcopenia increased from 16% to 33% for FLOT, and 14% to 30% in CROSS ( P <0.01 between arms). Median decrease in diffusion capacity for carbon monoxide was −8.25% (−34 to 25) for FLOT, compared with −13.8%(−38 to 29), for CROSS ( P =0.01 between arms). Major pathologic response was 27% versus 44% for FLOT and CROSS, respectively ( P =0.03). In-hospital mortality, respectively, was 1% versus 2% ( P =0.9), and Clavien Dindo >III 22% versus 27% ( P =0.59), however, respiratory failure was increased by CROSS, at 13% versus 3% ( P <0.001). Three-year survival was similar at 63% (FLOT) and 60% (CROSS) ( P =0.42). Conclusions: Both CROSS and FLOT resulted in equivalent survival. Operative outcomes were similar, however, the CROSS regimen increased postoperative respiratory failure and atrial fibrillation. Less than half of patients received the prescribed FLOT regimen, although toxicity rates were acceptable. These data support clinical equipoise, caution, however, may be advised with CROSS in patients with greatest respiratory risk.